2020
DOI: 10.3892/etm.2020.9500
|View full text |Cite
|
Sign up to set email alerts
|

miR‑155‑5p regulates macrophage M1 polarization and apoptosis in the synovial fluid of patients with knee osteoarthritis

Abstract: Osteoarthritis (OA) is one of the most prevalent degenerative joint diseases that affects millions of individuals worldwide. During OA, proinflammatory factors (including IL-1, IL-6, IL-17 and TNF-α) are released from chondrocytes and proliferating synoviocytes potentiate the proinflammatory microenvironment of the synovial fluid (SF). The altered SF microenvironment affects the infiltration, polarization and apoptosis of macrophages, though the underlying mechanisms are not completely understood. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…miR-155-5p can serve as the potential therapeutic target for KOA [ 6 ]. Our results demonstrated significantly upregulated miR-155 expression in LPS-induced chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-155-5p can serve as the potential therapeutic target for KOA [ 6 ]. Our results demonstrated significantly upregulated miR-155 expression in LPS-induced chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant study demonstrated indirect evidence of the role of chronic inflammation in patients with rheumatoid arthritis in metabolic syndrome and atherosclerosis development [ 5 ]. A variety of pro-inflammatory cytokines including interleukin 1 beta (IL-1β) and IL-18 secreted by an increased number of inflammatory cells exacerbate OA [ 6 , 7 ]. KOA affects 3 compartments of knee joints (patellofemoral, medial, and lateral joint), which usually slowly develops over 10–15 years and interferes with the daily life activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR155 is overexpressed and plays a key role in the pathophysiology of inflammatory diseases including autoimmune arthritis, osteoarthritis, periodontitis (11, 22, 53). An elevated level of miR155 in arthritis promotes M1 macrophage polarization and inflammation (53). Prevention of bone loss in inflammatory diseases using currently available therapeutic approaches is not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…A�������� �� � ����l� ����l���� c�ll ����� ���c��� ���� �� ���������l� ����l��� �� ��� ����l������, ����������� ��� ����� of various processes (30,31). As the most common chronic joint disease in the elderly population, OA is characterized by the progressive destruction of articular cartilage (32,33). Previous ������� ���� ����c���� ���� c������c��� ��������� �� c����l���� with the severity of OA (34,35).…”
Section: Discussionmentioning
confidence: 99%